CE and nanomaterials - Part II: Nanomaterials in CE - Adam, Vojtech; Vaculovicova, Marketa (Electrophoresis, 2017)
The scope of this two-part review is to summarize publications dealing with CE and nanomaterials together. This topic can be viewed from two broad perspectives, and this article is trying to highlight these two approaches: (i) CE of nanomaterials, and (ii) nanomaterials in CE. The second part aims at summarization of publications dealing with application of nanomaterials for enhancement of CE performance either in terms of increasing the separation resolution or for improvement of the detection. To increase the resolution, nanomaterials are employed as either surface modification of the capillary wall forming open tubular column or as additives to the separation electrolyte resulting in a pseudostationary phase. Moreover, nanomaterials have proven to be very beneficial for increasing also the sensitivity of detection employed in CE or even they enable the detection (e.g., fluorescent tags of nonfluorescent molecules).
Keywords: elektroforéza kapilární; liposomy; elektrolyty; nanotrubičky uhlíkové; Fluorescent Dyes; nanostruktury; Liposomes; fluorescenční barviva; Nanostructures; senzitivita a specificita; Electrolytes; Surface Properties; povrchové vlastnosti; Nanotubes, Carbon; Electrophoresis, Capillary; dendrimery; Sensitivity and Specificity; Dendrimers